2011
DOI: 10.1371/journal.pone.0018039
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Insect Species Competing for a Pulsed Resource: Toward a Unified Theory of Biodiversity in Fluctuating Environments

Abstract: BackgroundOne major challenge in understanding how biodiversity is organized is finding out whether communities of competing species are shaped exclusively by species-level differences in ecological traits (niche theory), exclusively by random processes (neutral theory of biodiversity), or by both processes simultaneously. Communities of species competing for a pulsed resource are a suitable system for testing these theories: due to marked fluctuations in resource availability, the theories yield very differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(108 citation statements)
references
References 39 publications
3
99
0
Order By: Relevance
“…This study thoroughly describes the endosymbiotic communities hosted simultaneously by four weevil sibling species that coexist, compete with each other for a limiting resource ( i.e ., oak acorns as egg-laying sites) [37,56,57] and display contrasted ecological traits [37,58]. We found that while all four species hosted the same primary endosymbiont, they harbored markedly distinct communities of secondary endosymbionts.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This study thoroughly describes the endosymbiotic communities hosted simultaneously by four weevil sibling species that coexist, compete with each other for a limiting resource ( i.e ., oak acorns as egg-laying sites) [37,56,57] and display contrasted ecological traits [37,58]. We found that while all four species hosted the same primary endosymbiont, they harbored markedly distinct communities of secondary endosymbionts.…”
Section: Discussionmentioning
confidence: 95%
“…These needs might differ from one host species to the other, notably when these ones interact in different ways with the same environment [11,64]. In the oak weevil communities, the marked ecological differences observed between the four species [37,58] would coincide with unequal probability for a given symbiont to spread. Conversely, we cannot rule out that the marked ecological differences between the four weevil sibling species might be due to the major symbionts having a distinct impact on their host.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such environmental variability could result in temporal niche partitioning, thereby increasing the variation of biological traits across species ( Chesson & Huntly 1997 , Venner et al 2011 ). However, the harshness of a variable environment may select against the coexistence of a high number of species [see Cohen (2004) for further discussion].…”
Section: Discussionmentioning
confidence: 99%